2004
DOI: 10.1007/s10329-004-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of genetic status in a closed colony of rhesus monkeys (Macaca mulatta)

Abstract: The long-term management of breeding colonies requires some measure of genetic diversity in the animal population. For the maintenance of breeding colonies of monkeys used for biomedical research, known pedigrees supply precise data to determine the genetic status of colonies. We present data of genetic analyses in an old closed colony of rhesus macaques (Macaca mulatta) that was established in 1932 with 100 animals. For more than 40 years, the animals were kept on an isolated island and, in 1980, single-male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 15 publications
(16 reference statements)
1
21
0
Order By: Relevance
“…DNA was extracted by an alkaline lysis procedure [SanCristobal-Gaudy et al 2000] and as detailed in Andrade et al (2004). PCR amplification of STRs was done in two 25 μL multiplexed reactions (groups A and B in Appendix A) each containing 1 μL of DNA template, 2.5 mM MgCl 2 , 200 μM dNTPs, 1X PCR buffer II (Applied Biosystems), 0.5 U Amplitaq (Applied Biosystems) and fluorescence-labeled primers in final concentrations given in Appendix A.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted by an alkaline lysis procedure [SanCristobal-Gaudy et al 2000] and as detailed in Andrade et al (2004). PCR amplification of STRs was done in two 25 μL multiplexed reactions (groups A and B in Appendix A) each containing 1 μL of DNA template, 2.5 mM MgCl 2 , 200 μM dNTPs, 1X PCR buffer II (Applied Biosystems), 0.5 U Amplitaq (Applied Biosystems) and fluorescence-labeled primers in final concentrations given in Appendix A.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from 5 to 10 mL heparinized peripheral blood by use of the Wizard Genomic DNA purification kit (Promega, California, USA). One-hundred and forty-eight microsatellite markers were selected for this study, including 104 markers reported in rhesus monkeys (Smith et al 2000;Hadfield et al 2001;Andrade et al 2004), 20 markers from the database of the CHLC (Cooperative Human Linkage Center: http://www.gai.nci.nih.gov/CHLC/), and 24 markers reported in major histocompatibility complex (MHC) associated reports of humans (Martin et al 1998;Foissac et al 2000). The primers were selected from the NCBI database (http://www.ncbi.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations by Andrade et al (2004), Doxiadis et al (2003Doxiadis et al ( , 2006, Ferguson et al (2007), Hernandez et al (2007), Smith (1998, 2004), Kanthaswamy et al (2006), Malhi et al (2007), Morin et al (1997), Penedo et al (2005), Satkoski et al (2007), and Viray et al (2001) have all characterized the genetic composition of rhesus macaque populations in the wild and in captivity. Most of these studies have reported discrete genetic differences between Indian and Chinese rhesus macaques and much greater genetic heterogeneity and substructuring in the latter than in the former.…”
Section: Introductionmentioning
confidence: 99%